Scope of practice in Primary Care: physicians and nurses in five health regions in Brazil - Sabado Nicolau Girardi; Ana Cristina de Sousa van Stralen; Thais Viana Lauar; Joana Natalia Cella; Jackson Freire Araújo; Célia Regina Pierantoni; Cristiana Leite Carvalho (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: The review on scopes of practice tends to gain importance in Human Resource in Health agenda in Brazil. The aim of this study was to investigate the scope of practice of physicians and nurses who work in the Atenção Primária em Saúde (APS) (Primary Healthcare) and their main barriers. Methods: this is an exploratory qualitative study conducted in 2015 and 2016, through interviews with 26 physicians and 26 nurses who work in the APS in 12 cities distributed in five Brazilian health regions. Results: physicians and nurses in the health region of the North and Northeast performed a great number of procedures, and those physicians who work in units located in rural areas. Both professional categories indicated that they knew how to carry out several procedures that were not performed in practice. The main barriers for not performing those procedures include, lack of access to exams, materials and inadequate infrastructure, protocols and city guides restrictions, legal restrictions and lack of training. Conclusions: the results suggests the need to ease the health professionals’ attributions, facilitate the integration between the professionals’ practices and optimizing their work, especially in remote and unassisted regions, in order to be in favor of expanding the access and problem solving in APS.